Lithium-induced apoptotic cell death is not accompanied by a noticeable inflammatory response in the kidney - Baranovskaya, Irina; Volk, Kevin; Alexander, Sati; Abais-Battad, Justine; Mamenko, Mykola (Frontiers in Physiology, 2024)
Lithium (Li+) therapy is a valuable tool in psychiatric practice that remains underutilized due to safety concerns. Excessive plasma Li+ levels are nephrotoxic and can trigger a local immune response. Our understanding of the immunomodulatory effects of Li+ in the kidney is fragmentary. Here, we studied how immune mechanisms contribute to the development of Li+-induced adverse effects in the kidneys of C57BL/6NJ mice placed on a 0.3% lithium carbonate diet for 28 days. We combined histochemical techniques, immunoblotting, flow cytometry, qPCR and proteome profiler arrays to characterize renal tissue damage, infiltrating immune cells and cytokine markers, activation of pyroptotic and apoptotic cascades in the kidneys of mice receiving Li+-containing and regular diets. We found that biomarkers of tubular damage, kidney injury marker, KIM-1, and neutrophil gelatinase-associated lipocalin, NGAL, were elevated in the renal tissue of Li+-treated mice when compared to controls. This correlated with increased interstitial fibrosis in Li+-treated mice. Administration of Li+ did not activate the pro-inflammatory NLRP3 inflammasome cascade but promoted apoptosis in the renal tissue. The TUNEL-positive signal and levels of pro-apoptotic proteins, Bax, cleaved caspase-3, and caspase-8, were elevated in the kidneys of Li+-treated mice. We observed a significantly higher abundance of CD93, CCL21, and fractalkine, accumulation of F4.80+ macrophages with reduced M1/M2 polarization ratio and decreased CD4+ levels in the renal tissue of Li+-treated mice when compared to controls. Therefore, after 28 days of treatment, Li+-induced insult to the kidney manifests in facilitated apoptotic cell death without an evident pro-inflammatory response.